Neural Dynamics of Olfactory Perception: Low- and High-Frequency Modulations of Local Field Potential Spectra in Mice Revealed by an Oddball Stimulus - Kum, Jeungeun; Kim, Jin Won; Braubach, Oliver; Ha, Jong-Gyun; Cho, Hyung-Ju; Kim, Chang-Hoon; Han, Hio-Been; Choi, Jee Hyun; Yoon, Joo-Heon (Frontiers in Neuroscience, 2019)
Recent brain connectome studies have evidenced distinct and overlapping brain regions involved in processing olfactory perception. However, neural correlates of hypo- or anosmia in olfactory disorder patients are poorly known. Furthermore, the bottom-up and top-down processing of olfactory perception have not been well-documented, giving difficulty in locating the disease foci of olfactory disorder patients. The primary aim of this current study is to characterize the bottom-up process of the neural dynamics across peripheral and central brain regions in anaesthetized mice. We particularly characterized the neural oscillations of local field potential (LFP) in olfactory epithelium (OE), olfactory blub (OB), prefrontal cortex (PFC), and hippocampus (HC) during an olfactory oddball paradigm in urethane anaesthetized mice. Odorant presentations evoked neural oscillations across slow and fast frequency bands including delta (1–4 Hz), theta (6–10 Hz), beta (15–30 Hz), low gamma (30–50 Hz), and high gamma (70–100 Hz) in both peripheral and central nervous system, and the increases were more prominent to infrequently presented odorant. During 5 sec odorant exposure, the oscillatory responses in power were persistent in OE, OB, and PFC, whereas neural oscillations of HC increased only for short time at stimulus onset. These oscillatory responses in power were insignificant in both peripheral and central regions of the ZnSO4-treated anosmia model. These results suggest that olfactory stimulation induce LFP oscillations both in the peripheral and central nervous system and suggest the possibility of linkage of LFP oscillations in brain to the oscillations in the peripheral olfactory system.